ITTO project PD 12/97 Rev.1 (F): forest, science and sustainability: the Bulungan model forest: technical report phase I, 1997-2001 - Center for International Forestry Research (CIFOR and ITTO, 2002)
CIFOR's research in the Bulungan Model Forest in Malinau, East Kalimantan, Indonesia took the form of a 3-year investigation into ways of achieving forest sustainability in a large forest landscape with diverse, rapidly changing and conflicting uses. The study reported in this book highligts the complexity of the challenge while also clarifying the key aspects. By understanding how the forest can yield timber, while also maintaining other important values to numerous stakeholders, by recognising the threat and institutional means available to address them, by understanding how the needs of the poorest communities of the forest see changes as both threats and opportunities, we can build up the understanding that decision makers need to make better decisions for sustainable forest management into the future. The research projects include: Reducing the impact logging on the forest; Biodiversity across the landscape; Forest people's dependency on forest products; and Coordination and agreement in boundary negotiation. The lessons learned from these researches provide baseline information that will support longer-term research.